PROGRAMA NACIONAL DE ALIMENTAÇÃO ESCOLAR E RECONHECIMENTO: UMA ANÁLISE EM COMUNIDADES RURAIS - Lopes, Edinéia (2017)
This study aimed to analyze the National School Feeding Program (PNAE) practices using Recognition Theory. Four theoretical categorieswere proposed based onNancy Fraser and José Henrique de Faria, which are economic, social, political, and emotional recognition of the farmers’ families who market to the PNAE of Rio Azul country. From this proposal, a field study was carried out usingqualitative methodological basis. Data were collected through documentary research in 2016 and semi-structured interviews between January and February 2017, being analyzed based on social theory discourse. The results reveal that PNAE provides recognition to the farmers’family in all categories presented,at the same time;it presents prac-tices that also deny recognition to individuals. PNAE participation allows interactions with theexternal environment, making visible the family farming products, and awakening a sense of belonging to the community, as well as learning from new working methods. The contact between farmers and PNAE is seen only as a relation of production and commercialization. In addition to the benefits provided by the program, there are also many barriers and difficulties for its entrance and continuity.Given the political, bureaucratic, and social interaction issues, the subjects belonging to PNAE need to re-evaluate the actions to the culture and develop-ment process of family agriculturedo not be lost.